Strengthening earthquake monitoring in Dubrovnik-Neretva County through collaboration between local municipality and scientific research community - Stipčević, Josip; Tomljanović, Mato (Crisis Management Days, 2025)
The integration of scientific expertise, governmental preparedness, and local governance is critical for effective earthquake monitoring and disaster response. This extended abstract presents a cooperative framework between the local municipality of Dubrovnik-Neretva County and the Department of Geophysics, Faculty of Science, to enhance earthquake preparedness and mitigation strategies. The collaboration focuses on establishing a robust earthquake monitoring network around Dubrovnik, incorporating 11 new seismic stations and distributed acoustic sensing (DAS) measurements. This initiative bridges scientific knowledge with policy-making and emergency response mechanisms to ensure the safety and resilience of communities in this seismically active region. 1. INTRODUCTION Seismic monitoring and disaster response require interdisciplinary collaboration to mitigate risks and enhance preparedness. Dubrovnik-Neretva County is located in a seismically active region, making earthquake monitoring a priority for local authorities. In response to this necessity, the local municipality has partnered with the Department of Geophysics, Faculty of Science, to develop an advanced earthquake monitoring system. This study explores the synergies between these entities, highlighting best practices and challenges in implementing a regional seismic network. 2. METHODS AND COLLABORATIVE FRAMEWORK The cooperation between Dubrovnik-Neretva County and the Department of Geophysics is based on several key initiatives. The establishment of a seismic network has been a priority, with 11 new seismic stations strategically deployed across the region to improve earthquake detection capabilities. These stations provide high-resolution seismic data essential for early warning systems and hazard assessment. In addition to traditional seismometers, the integration of Distributed Acoustic Sensing (DAS) technology, which utilizes fiber-optic cables to detect seismic waves, has enhanced real-time seismic monitoring and enabled the early detection of earthquake-related ground movements. Data sharing and communication have been strengthened through information exchanges between the Department of Geophysics and local authorities, ensuring immediate response capabilities in case of seismic activity. Public awareness and education have also been a major component of this collaboration, with educational campaigns and community outreach programs helping residents understand earthquake risks and preparedness measures. The scientific risk assessments provided by the Department of Geophysics are actively integrated into local urban planning, construction regulations, and emergency management policies to enhance long-term disaster resilience. 3. CASE STUDY: DUBROVNIK SEISMIC MONITORING NETWORK The seismic monitoring initiative in Dubrovnik-Neretva County serves as a model for regional earthquake preparedness. The installation of 11 seismic stations has provided comprehensive ground motion data, significantly improving earthquake detection and analysis. The use of DAS has further strengthened monitoring capabilities by offering continuous, high-resolution measurements of seismic activity. This collaborative project has demonstrated that close cooperation between scientific institutions and local authorities leads to more effective disaster risk management. 4. RESULTS AND DISCUSSION Preliminary results indicate that the Dubrovnik seismic network has enhanced earthquake detection accuracy and response efficiency. The integration of DAS technology has allowed for the detection of even minor seismic events, providing valuable data for hazard assessment. The collaboration has led to improved hazard prediction, increased public trust, and enhanced resource allocation for disaster preparedness. Despite these benefits, challenges such as funding sustainability, maintenance of seismic stations, and ensuring continuous data integration remain and require strategic policy adjustments to maintain long-term operational effectiveness. 5. FUTURE PERSPECTIVES To further enhance earthquake monitoring and response in Dubrovnik-Neretva County, future efforts should focus on expanding the monitoring infrastructure by increasing the number of seismic stations and enhancing the DAS network to cover a larger geographical area. The development of an early warning system based on real-time alert mechanisms is crucial to providing immediate warnings to residents and emergency responders. Strengthening cooperation with global and European seismic monitoring institutions will improve data exchange and predictive modeling capabilities. Additionally, continuous training programs for emergency responders and policymakers will ensure that all stakeholders remain prepared for future seismic events. 6. CONCLUSION The cooperation between Dubrovnik-Neretva County and the Department of Geophysics, Faculty of Science, marks a significant advancement in earthquake monitoring and disaster preparedness in the region. The establishment of an 11-station seismic network and the integration of DAS technology have enhanced real-time earthquake detection, ultimately improving public safety. Strengthening this collaboration through technological advancements, policy development, and public engagement is essential for mitigating earthquake-related risks. Future work should focus on expanding monitoring capabilities, implementing early warning systems, and fostering international cooperation to ensure long-term resilience against seismic hazards.